Non-uniform Convection Heat Transfer Characteristics of Supercritical Methane in 180° Curved Duct - HAN Chang-liang; YIN Peng; HAN Fang-ming; JIA Ji; XU Qi-ao; XIN Jing-qing; YAO An-ka (Journal of Harbin University of Science and Technology)
In order to reveal the heat transfer mechanism of supercritical methane (S-CH4) heat exchanger, the non-uniform convection heat transfer characteristics of supercritical methane (S-CH4) in a 180° curved duct are numerically analyzed. On the basis of verifying the reliability of the numerical method, the longitudinal and radial distribution of S-CH4 thermo-physical properties field and the distribution characteristics of “Dean vortices” are obtained, and the heat transfer capacity of curved duct and straight tube is compared. The results show that under the combined action of centrifugal force, gravity and continuous curvature of curved duct, the thermal properties of S-CH4 on the longitudinal section of curved duct present an obvious boundary line, and thermal-physical properties of S-CH4 on the radial section present the “non-concentric circle” distribution. The core position of “Dean vortices” is close to the inner wall of curved duct. At the same time, “Dean vortices” is helpful to enhance the heat transfer of S-CH4, the maximum value of local heat transfer coefficient locates in the inner wall of the curved duct. Compared with the straight tube, when the mass flux is 300 kg/m2·s and 600 kg/m2·s, the heat transfer coefficient of curved duct increases respectively by 18.8% and 23.5%. It provides a reference for the optimal design and application of S-CH4 heat exchanger.